Instructional Media Adding Blocks Game Knowledge Based on Numeracy in Operations Count Integer Load Mathematics - Ni Komang Prema Kumarasari; Anak Agung Gede Agung; I Gede Astawan (International Journal of Natural Science and Engineering, 2024)
Learning integer arithmetic operations in elementary schools still faces various challenges, especially in helping students understand concepts concretely. This study aims to develop and analyze the effectiveness of numeracy-based knowledge-enhancing block game learning media in improving students' understanding of integer arithmetic operations. The development model used is the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The subjects of this study were 25 fourth grade students. The data collection methods and instruments used were questionnaires and multiple-choice tests. The data analysis techniques used were qualitative descriptive, quantitative descriptive analysis and inferential statistical analysis. The results of the study showed that the use of this media significantly improved students' understanding of integer arithmetic operations, as evidenced by the increase in test results after the application of the media. In addition, students were more motivated and active in the learning process. The conclusion of this study is that numeracy-based knowledge-enhancing block game media is an effective and innovative learning tool. The implications of this study indicate that this media can be applied in activity-based learning and further developed for various other mathematical concepts.